12 Trends in Neck of Femur Fracture Incidence in EU15+ Countries From 1990–2017. (19th August 2022) - Ali, R; Sugand, K; Goodall, R; Salciccioli, J; Marshall, D; Schuster-Bruce, J; Abdul-Jabar, HB; Shalhoub, J
Abstract: Background: Neck of femur fractures (NOFF) pose significant socio-economic costs to society with a high degree of morbidity and mortality. Its incidence rate has been collated within the Global Burden of Disease (GBD) database; however, to date, no comparison across countries has been reported. Method: NOFF age-standardised incidence rates (ASIR) per 100, 000 population were extracted from the GBD database for European Union (EU) 15+ countries over the period 1990 to 2017. Joinpoint regression analysis of the data identified trends in ASIR and associated estimated annual percentage changes (EAPC). These were analysed by specified timeframe, country, and gender. Results: Of the 19 EU15+ countries, 11 (58%) had overall increases in NOFF ASIRs in 2017 compared to 1990. The median ASIRs were 240/100, 000 and 322/100, 000 for males and females, respectively, in 1990. By 2017, this had increased to 259/100, 000 and 325/100, 000, respectively. Females consistently had relatively higher NOFF ASIRs with a median gender fracture gap of 62/100, 000 in 2017. Males had a higher percentage change in increasing ASIRs, with a smaller percentage change in decreasing ASIRs for all included countries. The highest national ASIRs was observed in Australia, followed by Finland and Belgium. Conversely the Mediterranean countries demonstrated the lowest ASIRs, closely followed by the USA. Conclusions: Despite significant advances in primary and secondary hip fracture prevention strategies over the 28-year study period, significant increases in NOFF ASIRs among most EU15+ countries were observed, especially with respect to gender.